The characterization of glass fibre reinforced unsaturated polyester filled with P84 Polyimide / Multi-Wall Carbon Nanotubes (MWCNT) hybrid composites / Nik Noor Idayu Nik Ibrahim - Nik Ibrahim, Nik Noor Idayu (2017)
This study was carried out with an aim to improve the strength and thermal stability of the glass fibre reinforced unsaturated polyester composites by incorporating the P84 Polyimide powder and Multi-wall Carbon Nanotubes (MWCNT) as filler. Research methodology for this study was divided into four main stages. First stage is the preliminary study on the effect of the masterbatch technique on the basic properties of unsaturated polyester. Masterbatch technique is the mixing of powder P84 Polyimide with liquid MEKP prior to be incorporated into the polyester resin, where a mixture that contain both filler and curing agent was produced. This mixture was prepared in bulk, stored in a closed container and only taken out when needed. The results showed that the masterbatch technique does not affect the gel time but does increased the Tg. The second stage was the preparation of the matrix-filled system as a function of different preparation techniques where two matrix systems were studied. First was the unsaturated polyester filled with masterbatch P84 Polyimide system and the second was the unsaturated polyester filled with P84 Polyimide system. The difference between the systems was the preparation technique. The first system was prepared by incorporating both filler and curing agent (masterbatch P84 Polyimide) simultaneously into the polyester resin. The second system was prepared by incorporating filler and curing agent in separate steps. The incorporation of P84 Polyimide into the unsaturated polyester through the masterbatch technique resulted in the increment in tensile strength with the increased amount of filler loading. Third stage was the treatment of glass fibre with 3-Aminopropylethxysilane. The treatment was considered successful in attaching the silanol species on the surface of glass fibre where the molecular vibration of amino organofunctional group; C-N and N-H, was detected in FTIR spectrum. The fourth stage was the fabrication of glass fibre reinforced unsaturated polyester filled with P84 Polyimide/MWCNT hybrid composite and the composites were analysed based on the physical, mechanical, and thermal properties and also the morphological observation of the fractured samples. In a nutshell, the addition of P84 Polyimide at lower loading into the unsaturated polyester matrix system improved the strength of the composite. However, at higher filler loading, the strength dropped and worsens with the increasing number of glass fibre laminates. On the other hand, the incorporation of MWCNT caused the reclining in strength due to the incomplete broken down of coiled MWCNT. Nevertheless, the hybridization of MWCNT with P84 Polyimide able to raise back the strength. Thus, most of the mechanical properties showed by the hybrid composites were in between the unfilled composites and single filler composites. Through the morphological observation, the difference in texture and failure modes between single filler and hybrid filler composites were observed.